The Cambridge handbook of violent behavior and aggression - Flannery, Daniel J., 1962-; Vazsonyi, Alexander T., 1964-; Waldman, Irwin D. (Cambridge handbooks in psychology., 2007)
Examines a range of theoretical, policy, and research issues and provides a comprehensive overview of aggressive and violent behavior.